Applied accounting of the public and business sectors in Venezuela (Gestión y Gerencia, 2019)
In order to evaluate and incorporate the essential principles that define accounting as applied science in the different administrative units of the public and private sectors in Venezuela, a general vision is built on the accounting of the Public Sector and the Business Sector in the country on the basis of a literature review of texts, laws and regulations. A documentary work about the concept of accounting as science is developed, as well as the types of norms and general instruments of registration in Venezuela, and its function and objectives in public and private organizations. The result allows to present a systematized study and / or chronicle about the subject in a general and particular framework for the area in the country
Keywords: Accounting; Method; Public Sector; Business; Venezuela